Quantum Microscopy of Biological Systems - Taylor, Michael (Springer, 2016)
This thesis reports on the development of the first quantum enhanced microscope and on its applications in biological microscopy. The first quantum particle-tracking microscope, described in detail here, represents a pioneering advance in quantum microscopy, which is shown to be a powerful and relevant technique for future applications in science and medicine.